Phenomenology of human rights the new Commission on Human Rights building - Vargas, Vargas III M. (Quezon City College of Architecture, University of the Philippines Diliman, 2014)
This research examines phenomenology as a guiding principle and concept in developing a design for a new Commission on Human Rights building.
The research starts with the design problem of designing a new Commission on Human Rights building which will provide the experience of human rights to its users. The research identified two user types that use the building the private staff and the public. The public is further divided into two types: the vulnerable group and the five pillars of justice.
The phenomenology of human rights is subjective to each user group. Each user group has a distinct user experience provided in the design of the building.
The research ends with a design which provides a different user experience for the private staff, the vulnerable group, and the five pillars of justice group.
Thesis (Bachelor of Science in Architecture)--University of the Philippines Diliman